Language, behavior and neurodevelopment in Joubert syndrome: A case report - Lamônica, Dionísia Aparecida Cusin; Ribeiro, Camila da Costa; Richieri-Costa, Antonio; Giacheti, Célia Maria [UNESP] (FapUNIFESP (SciELO), 2016)
The Joubert syndrome (JS) is a rare, heterogeneous genetic condition among the ciliopathies. More than 20 genes have been identified associated with this phenotype. The main manifestations include hypotonia, ataxia, psychomotor retardation, ocular-motor apraxia and neonatal respiratory abnormalities. The objective of this paper was to present language and neurodevelopmental findings of an individual diagnosed with JS. The following procedures were performed: anamnesis, clinical genetic evaluation observation of communicative behavior, evaluation of language, the Denver Developmental Screening Test II (DDST-II) and the Early Language Milestone Scale (ELMS). The main findings of the MRI brain showed severe hypoplasia of the cerebellar vermis, molar tooth sign, hypoplastic brain stem and atrophy of the cerebellar hemispheres. The observation and evaluation of the language showed no oral, impaired reception of language, confirming the diagnosis of language disorder with severe degree of impairment. The DDST-II and the ELMS confirmed the observation and clinical assessment and indicated serious delay in motor domains, self-care and receptive and expressive language. Given the presence of hypotonia, ataxia, delayed psychomotor and neonatal respiratory abnormalities it is essential to carry out examination imaging and genetic evaluation for the diagnosis of this condition, so complex, with unique therapeutic needs. This set of findings, along with the familial history and unique phenotypic characteristics reinforce the clinical genetic diagnosis JS. This genetic syndrome is rarely recognized and deserves to be presented to the recognition of the scientific community, targeting the correct diagnosis and treatment planning that minimizes the deleterious effects of this condition.
Keywords: Behavior; Child development; Child language; Joubert syndrome; Psychomotor performance